Influence of Front and Back Contacts on Photovoltaic Performances of p-n Homojunction Si Solar Cell: Considering an Electron-Blocking Layer. (12th March 2017) - Ali, Md. Feroz; Hossain, Md. Faruk
Abstract : In this simultion work, the effect of front and back contacts of p-n homojunction Si solar cell with an electron-blocking layer (EBL) has been studied with the help of a strong solar cell simulator named AMPS-1D (analysis of microelectronic and photonic structures one dimensional). Without the effect of these contact parameters, low solar cell efficiency has been observed. Fluorine-doped tin oxide (FTO) with high work function (5.45 eV) has been used as the front contact to the proposed solar cell. Zinc (Zn) metal which has a work function of 4.3 eV has been used as the back contact of the proposed model. With FTO as the front contact and Zn as the back contact, the optimum efficiency of 29.275% (Voc = 1.363 V, Jsc = 23.747 mA/cm 2, FF = 0.905) has been observed. This type of simple Si-based p-n homojunction solar cell with EBL of high efficiency has been proposed in this paper.